‘Travelling Without Moving’ and ‘Transformation, Identity and Liminality in Travel Memoir’ - King, Laura Tanja (Curtin University, 2015)
This thesis comprises a creative work and an exegesis. The creative work, Travelling Without Moving, is an autobiographically-inspired, fictional, discontinuous travel narrative that explores why and how we navigate our inner and outer journeys, and correlates the suffering of the world that surrounds us with the uncharted elements—confusion, passion, evil—of our inner lives. The exegesis considers how travel memoirs question our liminal encounters with the ‘other’ and the affective transformation of our identity.